The Problem of Alcohol in Colonial India (c. 1907–1942). (August 2017) - Bhattacharya, Nandini
This article traces the transformation of liquor and industrial alcohol into a commercial product in twentieth-century colonial India. Liquor (alcoholic beverages for human consumption) remained prominent in political discourse and in the public sphere in this period. Temperance activists, Gandhian nationalists and medical authorities critiqued government revenue extraction from consumable liquors and advocated either partial or total prohibition. On the other hand, industrial alcohol emerged as an unchallenged and untampered commodity while it became essential to Indian industrialization, a process that accelerated between the wars. This article moves beyond cultural explanations of transformation of commodities and instead focuses on the temporal and political lives of liquor and alcohol in colonial India.